Studi Pola Penggunaan Obat Anti Tuberkulosis pada Pasien Tuberkulosis Paru - Andrea Verencia Naftali; Gilang Rizki Al Farizi; Ovikariani Ovikariani (Jurnal Surya Medika (JSM), 2022)
Tuberculosis is one infectious disease that is still a significant problem in the health sector. This study aims to determine the pattern of anti-tuberculosis drugs in pulmonary tuberculosis patients, including the right dose, right patient, right time of administration, right route of administration, and alert for side effects based on the 2017 National Guidelines for Tuberculosis Control. The method used is descriptive with data collection systematically. Retrospectively in the form of medical record data for 2019 to 2020 at the Semarang Barat District Health Center, Semarang City, namely as many as 35 pulmonary tuberculosis patients. The study of drug side effects was traced based on the literature from several journals. The results of the univariate analysis showed that the use of anti-pulmonary tuberculosis drugs was obtained 100% at the right dose, 100% by the right patient, 100% at the time of administration, and 100% correct method of administration. Meanwhile, the side effects of using fixed-dose combination category 1 anti-tuberculosis drugs based on the literature are nausea, vomiting, redness of the urine, fever, lack of appetite, itching, and skin redness. The use of drugs in pulmonary tuberculosis patients at the Semarang Barat District Health Center, Semarang City, is in by the 2017 National Guidelines for Tuberculosis Control, a reference for the appropriate use of anti-tuberculosis drugs.